Redefining Europe's economic sovereignty - Mark Leonard; Jean Pisani-Ferry; Elina Ribakova; Jeremy Shapiro; Guntram B. Wolff (Bruegel, 2019)
Europeans like to believe the European Union has the collective economic size and capacity to determine its own economic destiny. But the behaviour of others global powers is increasingly calling this ability into question. China and the United States, especially, do not separate economic interests from geopolitical interests in the same way the EU does. They are increasingly using economic connections, from cyberspace to financial links, to gain geopolitical advantage or to serve geopolitical goals. Europe's economic sovereignty is at stake. The problem for Europe is real but manageable. This Policy Contribution examines the specific problems that China and the US pose for European economic sovereignty, and considers how the EU and its member states can better protect European economic sovereignty in a range of areas, including state aid to domestic industries, competition policy, investment screening, export controls, the international role of the euro, the role of European development banks, the European payments infrastructure and the global governance system. In each area, we recommend ways to improve the EU's capacity to wield economic power, without advocating increased protectionism or a retreat from globalisation. We make recommendations on how to adapt the EU and national policy systems to better integrate economic and geopolitical considerations. The next European Commission should develop an economic sovereignty strategy to boost Europe's research and scientific base, protect assets critical to national security from foreign interference, enforce a level playing field in domestic and international competition, and strengthen European monetary and financial autonomy. To guide the implementation of this strategy, an economic sovereignty committee should be established that will seek to integrate economic and security considerations within the European Commission. But the answer to this problem does not lie only in Brussels. We recommend a flexible implementation strategy that connects with member-state policy debates and makes use of 'mini-lateral' groups of member states.
Keywords: 330